Influential theories of economics in shaping sustainable development concepts - Faruque As Sunny; Eila Jeronen; Juping Lan (Administrative Sciences, 2025)
This study explores the pivotal role of theories of economics in shaping the multifaceted concept of sustainable development and integrates economic, social, and environmental dimensions. It traces the intellectual trajectory of classical, neoclassical, and contemporary economic paradigms, analysing their contributions to sustainability-oriented policies and practices. The study critically analyses key concepts, including equitable income redistribution, resource stewardship, and ecological preservation. It contrasts liberal and dependency theories while also comparing insights from environmental and ecological economics. Employing a rigorous literature review and comparative analytical methodology, the study bridges the theoretical foundations with real-world applications, illustrating the dynamic interplay between theories of economics and sustainability imperatives. The findings elucidate the dichotomy between weak and strong sustainability frameworks, advocating for ethical and interdisciplinary approaches to policymaking. By offering a comprehensive synthesis of the most influential theories of economics and sustainable development practices, this study provides profound insights for policymakers, academics, and practitioners seeking to address pressing global challenges through informed and integrative strategies.
Keywords: 350; economics; theories; sustainable development; resource management; environmental economics; weak and strong sustainability; ethics; policy